Effect of solvent and substrate temperature on morphology of cerium oxide thin films by simple nebuliser spray pyrolysis technique. (January 2015) - Suresh, R.; Ponnuswamy, V.; Mariappan, R.
Abstract : Cerium oxide thin films are coated on glass substrates by nebuliser spray pyrolysis technique. The crystallographic structures, surface morphology, optical properties and I–V characteristics have been studied as a function of solvent and substrate temperature (300–500°C). X-ray diffraction was used to estimate crystallographic texture, grain size, strain and lattice constant. All films exhibit cubic fluorite structure with different preferred orientations depending on the preparation conditions. Photoluminescence spectra revealed the presence of violet and blue emissions in the visible region. The calculated band gap energy is found to be in the range 3·0 to 3·6 eV. Spherical and lamellar shaped particles with crystallite size 10–41 nm are found in the film surface. X-ray photoelectron spectroscopy analysis confirms the highly non-stoichiometric nature of the films with dominant occurrence of Ce 4+ (CeO2 ) and subsidiary occurrence of Ce 3+ (Ce2 O3 ).